Resilient modulus of a compacted clay with different moisture and temperature histories. Issue 1 (6th December 2023) - Han, Zhong; Ding, Lu-qiang; Feng, Huai-ping; Yang, Guang-qing; Zou, Wei-lie
ABSTRACT: This paper reports a series of experimental studies to compare the influences of different moisture and temperature histories on the resilient modulus ( M R ) of a compacted clay. Parallel specimens that were compacted at the optimum moisture content ( w opt ) were equilibrated to six different moisture contents ( w ) and subjected to different numbers of freeze–thaw cycles ( N FT = 0, 1, 3, 10) before determining the M R and the unconfined compressive strength (UCS). Specimens were brought to each testing condition (i.e. the combination of w and N FT ) through two or three different interlaced wetting-drying and freeze–thaw processes. Such a procedure imposed different moisture and temperature histories on the specimens. Experimental results demonstrated that different moisture and temperature histories only result in noticeable differences in the M R for specimens tested at the dry side of the w opt and N FT = 1. The differences become negligible at all w levels after freeze–thaw effects have stabilised at N FT = 10. Different Moisture and temperature histories do not differentiate the relationships of the M R and UCS to the w and N FT . Meanwhile, the relationships of the M R to the UCS are unique and linear regardless of the different moisture and temperature histories.